PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP MINAT BELAJAR KIMIA PESERTA DIDIK - Wisnu Prammana Surya; Indyah Sulistyo Arty (Jurnal Kependidikan, 2020)
This study aims to determine the effect of applying the problem based learning (PBL) learning model to students' interest in learning chemistry on the topic of chemical equilibrium. This research is a quantitative research type of quasi experiment using posttest only design. The study was conducted at SMA Negeri 6 Pekanbaru. The sample was determined using simple random sampling technique. Data on students 'interest in learning chemistry are collected using a questionnaire based on five categories, namely the level of students' interest in chemistry, personal choice, teacher's role, situational interest, and willingness to attend chemistry learning. Quantitative data were analyzed using mean, standard deviation, percentage, and One-Way ANOVA hypothesis testing. Descriptive analysis is used to describe the interest in learning chemistry. The results showed that there were significant differences in interest in learning chemistry between students applying PBL learning models and expository learning models on the topic of chemical equilibrium. Interest in learning chemistry of students is still relatively low, but students who use the PBL model show higher scores than expository classes. Male students are more interested in chemistry than female students.